Estimating the Public Health and Economic Impact of Annual mRNA COVID-19 Vaccination for Adults Aged 50 and Older in South Korea’s Endemic Era - Jaehee Jung; Dain Lee; Hee-Do Yang; Ah-Young Kim; Haeun Lee; Minkyoung Kang; Ekkehard Beck; Keya Joshi; Youngju Kang; Hye-Young Kang (Vaccines)
Background/Objectives: COVID-19 continues to challenge public health due to emerging variants. To mitigate this, the Korea Disease Control and Prevention Agency (KDCA) recommends annual COVID-19 vaccination, but uptake remains suboptimal. This study evaluates the public health and economic impact of annual mRNA COVID-19 vaccination for adults aged 50 and older in South Korea during the 2024–2025 season, focusing on hospitalizations and costs. Methods: We estimated hospitalizations prevented by the mRNA-1273 XBB.1.5 containing vaccine by calculating symptomatic infection incidence rates, hospitalization rates among unvaccinated individuals, vaccine effectiveness (VE) against hospitalization, and vaccination rates. Incidence rates among the unvaccinated with an annual vaccine were derived by adjusting overall infection rates based on vaccination coverage and VE against COVID-19 hospitalization rates. Hospitalization costs were obtained from a real-world dataset, integrating the KDCA’s COVID-19 confirmed cases with National Health Insurance claims data. Comparative analyses between mRNA-1273 and BNT162b2 used published meta-analysis results. Results: Assuming vaccination rates remain consistent with the 2023–2024 season, mRNA-1273 is projected to prevent 37,200 hospitalizations and save USD 77.2 million in healthcare costs during the 2024–2025 season compared to no annual vaccination. Compared to BNT162b2, it is expected to prevent an additional 13,260 hospitalizations saving USD 27.5 million. If vaccination rates increased to match influenza, hospitalizations prevented by mRNA-1273 could rise to 79,800 with USD 164.2 million in healthcare savings compared to no annual vaccination. Conclusion: Annual mRNA COVID-19 vaccination with mRNA-1273 substantially reduces hospitalizations and healthcare costs. Increasing vaccination rates are essential to maximize public health benefits.